Perceived HIV-associated stigma among HIV-seropositive men: psychometric study of HIV stigma scale - Adrian eValle; Ana Cecilia Treviño; Farith Francisco Zambrano; Karla Elizabeth Urriola; Luis Antonio Sánchez; Luis Antonio Sánchez; Jesus Eduardo Elizondo; Jesus Eduardo Elizondo; Jesus Eduardo Elizondo (Frontiers Media S.A., 2015)
Objectives: To assess the internal consistency and factor structure of the abridged Spanish version of the Berger HIV Stigma Scale (HSS-21), provide evidence for its convergent and discriminant validity, and describe perceived stigma in an urban population from northeast Mexico. Methods: Seventy five HIV-positive men who have sex with men (MSM) were recruited. Participants answered the Spanish versions of three Likert-type scales: HSS-21, Robsenberg's self-esteem scale, and the abbreviated version of the Zung's Depression Scale.Results: HSS-21 showed high reliability and validity; its factor structure included four components: concern with public attitudes; negative self-image; disclosure concerns; and enacted stigma. The level of stigma was high in 27 out of 75 (36%) participants; nevertheless, the score found in the component related to disclosure concerns indicated high level of stigma in 68% of participants. The score of HSS-21 was positively correlated with the score of depression and negatively correlated with the score of self-esteem. Conclusion: Results demonstrated high reliability for the HSS-21; correlations with other scales supported its validity. This scale demonstrated to be a practical tool for assessing stigma among Mexican HIV-positive MSM. High level of stigma was found only in the factor related to disclosure concerns. Policy Implications: Identifying HIV-associated stigma through a short, reliable and validated instrument will allow the development of interventions that cope and manage stigma in HIV-positive MSM. HSS-21 distinguishes between different dimensions of stigma and will contribute to a better understanding of this phenomenon.